GOVERNMENT RESPONSIBILITY TO HIGHER EDUCATION FOR AFGHANISTAN REFUGEE IN INDONESIA - Rizka Safna Amanda; M. Ya’kub Aiyub Kadir (Universitas Syiah Kuala, 2023)
The article investigates Indonesian responsibility under international law to Afghanistan refugee on how far Indonesian government has provided educational rights to Afghanistan refugee, and how far the cooperation between Universities and UNHCR related to the implementation of the higher education of refugees in Indonesia. The data was gathered through library research and field investigation using a normative-empirical strategy. Literature research was conducted by studying books, public files on the official UNHCR website. Indonesia has not ratified the 1951 Convention and the 1967 Protocol relating to the status of refugees. However, Indonesia has ratified the Convention on the Rights of the Child (CRC) and the International Covenant on Economic, Social and Cultural Rights (ICESCR) which indicates that refugees are entitled to basic rights such as the right to education, which refers to basic education excluded higher education. It is suggested that the Indonesian government develop a sound legal products related to the right to education for refugees, ranging from basic education to higher education.